E-WOM INFLUENCE ON ACTUAL SAVING BEHAVIOR AT BSI WITH INTEREST AND TRUST MEDIATION - Istiqomah, Azizatul; Siswanto; Yayuk Sri Rahayu (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2025)
The Islamic banking industry in Indonesia has grown significantly over the past decade as public awareness of Sharia-compliant financial services continues to rise. However, participation among younger generations, particularly Generation Z, remains relatively low despite their characteristics as digital natives who are critical of information and prefer practical services aligned with Islamic values. This study examines the influence of Electronic Word of Mouth (E-WOM) on actual saving behavior at Bank Syariah Indonesia (BSI), with saving interest and trust serving as mediating variables. Using a quantitative approach, data were collected from 104 Generation Z respondents in Malang City and analyzed through Structural Equation Modeling (SEM) with SmartPLS 3.0. The findings reveal that E-WOM significantly influences saving interest, trust, and actual saving behavior. Saving interest and trust also function as mediators that strengthen the relationship between E-WOM and saving behavior. These results indicate that digital exposure such as reviews, testimonials, and positive customer experiences can increase interest, build trust, and ultimately encourage concrete financial actions, including opening or maintaining savings accounts. The study concludes that E-WOM-based communication strategies are essential for Islamic banks to attract Generation Z and enhance engagement with Sharia-compliant saving products.